Expression and Function of Chemokines CXCL9-11 in Micturition Pathways in Cyclophosphamide (CYP)-Induced Cystitis and Somatic Sensitivity in Mice - Guo, Michael; Chang, Phat; Hauke, Eric; Girard, Beatrice M.; Tooke, Katharine; Ojala, Jacqueline; Malley, Susan M.; Hsiang, Harrison; Vizzard, Margaret A. (Frontiers in Systems Neuroscience, 2018)
Changes in urinary bladder function and somatic sensation may be mediated, in part, by inflammatory changes in the urinary bladder including the expression of chemokines. Male and female C57BL/6 mice were treated with CYP (75 mg/kg, 200 mg/kg, i.p.) to induce bladder inflammation (4 hr, 48 hr, chronic). We characterized the expression of CXC chemokines (CXCL9, CXCL10 and CXCL11) in the urinary bladder and determined the effects of blockade of their common receptor, CXCR3, at the urinary bladder level on bladder function and somatic (hindpaw and pelvic) sensation. qRT-PCR and ELISAs were used to determine mRNA and protein expression of CXCL9, CXCL10, and CXCL11 in urothelium and detrusor. In urothelium of female mice treated with CYP, CXCL9 and CXCL10 mRNA significantly (p ≤ 0.01) increased with CYP treatment whereas CXC mRNA expression in the detrusor exhibited both increases and decreases in expression with CYP treatment. CXC mRNA expression in the urothelium and detrusor of male mice was more variable with both significant (p ≤ 0.01) increases and decreases in expression depending on the specific CXC chemokine and duration of CYP treatment. CXCL9 and CXCL10 protein expression was significantly (p ≤ 0.01) increased in the urinary bladder with 4 hr CYP treatment in female mice whereas CXC protein expression in the urinary bladder of male mice did not exhibit an overall change in expression. CXCR3 blockade with intravesical instillation of AMG487 (5 mg/kg) significantly (p ≤ 0.01) increased bladder capacity, reduced voiding frequency and reduced non-voiding contractions in female mice treated with CYP (4 hr, 48 hr). CXCR3 blockade also reduced (p ≤ 0.01) hindpaw and pelvic sensitivity in female mice treated with CYP (4 hr, 48 hr). CXC chemokines may be novel targets for treating urinary bladder dysfunction and somatic sensitization resulting from urinary bladder inflammation.